Azamacrocyclic nickel(II) and copper(II) complexes bearing aryl substituents: synthesis, properties, and crystal structures - Tsymbal, Lyudmyla V.; Andriichuk, I. L.; Lampeka, Ya. D.; Pritzkow, Hans (Russian chemical bulletin, 2010)
A synthetic procedure for preparation of new amphiphilic copper(II) and nickel(II) azamacrocyclic complexes bearing aromatic substituents is developed. The nature of substituents is shown to exert a negligible influence on spectral and electrochemical characteristics of the prepared compounds. The X-ray diffraction analysis of three copper complexes revealed the formation of the dimers of macrocyclic cations associated by noncovalent interactions, nature of which is determined by the structure of the substituent in the macrocyclic ligand.